PENURUNAN PERSEPSI NYERI PASIEN KANKER MENGGUNAKAN METOOE "AFFIRMASITAPPING TECHNIQUE" 01 WILAYAH KERJA PUSKESMAS PACARKELING SURABAYA - Joko suwito; Padoli .; Dhiana Setyorini; Intim Cahyono (JURNAL PENELITIAN KESEHATAN, 2015)
Affirmation-Taping Techniques (An) has shown good results and safe as an alternative to reduce theperception of pain after surgery. NeverthelessAn therapy to reduce the perception of pain in patientswith cancer outpatient health center hasnot been confirmed usefulness.The design of this study is a quasi experimental pre-posttest control group design, with a population ofcancer patients who are actively participating in outpatient health center PacarkelingSurabaya, in a simplerandomized into the control group and the treatment group; has signed a Letter of Approval and followAn after receiving an explanation. The research instrument with the Visual Analogue Scale (VAS) and theMcGill-Melzack Pain Questionare and An's Guide; Data were analyzed with the Kolmogorov-Smirnove.Ethical clearance was obtained from the Health Research Ethics Committee (IEC) of Ministry of HealthPolytechnicof Surabaya.Treatment with An group amounted to 10 (ten) and a control group of 10 (ten); the two groups allgained a basic drug therapy in an outpatient health center services Pacarkeling Surabaya. From theanalysis of the hypothesis test is obtained that An has shown a significant difference in reducing theperception of pain cancer patients compared to controls (p = 0.000; a = 0.05).Discussion: An which is the technique of psycho-behavioral therapy treatment, the theory of SelfAffirmationand Meridian Theory-acupuncture; has changed the perception-emotion-koqnition is notconstructive toward self-acceptance and trust and hope in God Almighty, then reinforced by tapping onacupuncture points that reinforce the perception-koqnition-constructive emotion. Prefrontal cortex,hippocampus, amygdala and thalamus translate these conditions to produce neurotransmitters, which inturn c~n activate brain plasticity to modulate the pain and reduce the perception of painKey words: Pain perception, Affirmation Tapping Techniques, Cancer patient